Lactobacillus fermentum CECT5716 Supplementation in Rats during Pregnancy and Lactation Impacts Maternal and Offspring Lipid Profile, Immune System and Microbiota - Azagra-Boronat, Ignasi (Cells, 2020)
Probiotics have shown potential for their use in early life. This study aimed to investigate whether the administration of Lactobacillus fermentum CECT5716 during pregnancy and lactation periods impacts maternal and offspring plasma lipid profile, immune system and microbiota. Rats were supplemented with the probiotic during gestation and two weeks of lactation. After supplementation, although the microbiota composition was not affected, the probiotic strain was detected in all cecal contents of dams and in some of their pups. Dams showed reduced proportion of T cytotoxic cells in the mesenteric lymph nodes, modulation of intestinal cytokines (IL-10 and IL-12) and changes in plasma fatty acids (20:0, 22:0, 20:5 n-3, and 18:3 n-6). Pups showed changes in immunoglobulins (intestinal IgA and plasmatic IgG2a and IgG2c) and fatty acid profile (17:0, 22:0, and 18:2 n-6). Overall, Lactobacillus fermentum CECT5716 supplementation contributed to beneficially modulating the immune system of the mother and its offspring.